Chemical redistribution and change in crystal lattice parameters during stress relaxation annealing of the AD730TM superalloy. (15th September 2022) - Durand, Malik; Cormier, Jonathan; Paumier, Fabien; Katnagallu, Shyam; Saksena, Aparna; Kontis, Paraskevas; Pettinari-Sturmel, Florence; Hantcherli, Muriel; Franchet, Jean-Michel; Dumont, Christian; Bozzolo, Nathalie
Abstract: The present study aims to understand the underlying mechanisms of macroscopic contraction that occurs in γ/γ′ nickel based superalloys submitted to isothermal annealing and resulting in stress relaxation retardation. Samples of the AD730 TM alloy were characterized at different scales using dilatometry, X-Ray Diffraction (XRD) with in-situ heating, Electron Channeling Contrast Imaging (ECCI) in the Scanning Electron Microscope (SEM), conventional Transmission Electron Microscopy (TEM) and Atom Probe Tomography (APT). APT analyses revealed chemical composition changes in both the γ matrix and the γ′ hardening precipitates during annealing at 760°C after sub-solvus solution heat treatment. These chemical alterations lead to a decrease of the lattice parameters of both phases, which was captured by XRD analyses. The macroscopic volume contraction is shown to be mainly governed by that decrease in the lattice parameters. In addition, from APT analyses, the chemical alterations seem to be promoted by diffusion of solutes such as Cr, Co and Fe, along dislocations occurring under relaxation testing conditions. Graphical abstract: Image, graphical abstract